CHIANTI—An Atomic Database for Emission Lines. XVII. Version 10.1: Revised Ionization and Recombination Rates and Other Updates - Kenneth P. Dere; G. Del Zanna; P. R. Young; E. Landi (The Astrophysical Journal Supplement Series, 2023)
The CHIANTI atomic database provides sets of assessed data that are used for simulating spectral observations of astrophysical plasmas. This article describes updates that will be released as version 10.1 of the database. A key component of CHIANTI is the provision of ionization and recombination rates that are used to compute the ionization balance of a plasma over a range of temperatures. Parameters for calculating the ionization rates of all stages of ions from H through Zn were compiled and inserted into the CHIANTI database in 2009. These were based on all measurements that were available at the time and supplemented with distorted wave calculations. Since then, there have been a number of new laboratory measurements for ions that produce spectral lines that are commonly observed. Parameters have been fit to these new measurements to provide improved ability to reproduce the ionization cross sections and rate coefficients, and these are added to the database. CHIANTI 10.1 also includes new recombination rates for the phosphorus isoelectronic sequence, and the updated ionization and recombination rates have been used to calculate a new ionization equilibrium file. In addition, CHIANTI 10.1 has new electron collision and radiative data sets for eight ions in the nitrogen and oxygen isoelectronic sequences and updated energy level and wavelength data for six other ions.